SISTEM PENDAFTARAN MAHASISWA BARU BERBASIS ANDROID - Rosdiana Devi, Adelia; Raynanda Desmadhani, Phryzia; NADZIROH, FARIDATUN (UPPM Akademi Komunitas Semen Indonesia, 2022)
Along with the development of technology, people are more likely to read and obtain information through smartphones that are easier to access anywhere and anytime. The development of information technology is very welcomed by all among one of them in the world of education which is used to create a new student registration system. Therefore the new student registration information system based on Android is needed to simplify and accelerate in terms of registration for prospective students to register and can facilitate the process of registering data and data stored in a computerized information system. The making of an android-based new student registration information system at the Semen Indonesia Gresik Community Collage was built using MIT App Inventor software, SQLyog, PHP Runner and XAMPP. This system has a database for storing data and entering and retrieving the data needed. This system is made with work procedures for data collection, system analysis, design, system, implementation, and system testing. This application can also be used to access information on new student admissions such as academic selection schedules, tuition fees, registration of new student admissions, and announcements. So that prospective new students can get information and register easily and efficiently.